Towards an institutional view of mapping corporate social responsibility meanings - Golob, Urša (Teorija in praksa, 2011)
This paper addresses the social meaning of corporate social responsibility (CSR), taking into account the context of the economic crisis in Slovenia. The objective is to map out the semantic content of CSR in an attempt to capture the ideas that individuals associate with this concept and to contrast it with the pre-defined conceptualisations that are often a basis for examining CSR perceptions. To achieve this we conducted a semantic network analysis of free CSR associations. The findings suggest that the social meaning of CSR is anchored in the perception of business responsibility showing the implicit character of the meaning of CSR.
Keywords: Družbena odgovornost; Social responsibility; Institucionalizem; Institutionalism; Network analysis; Analiza omrežij; Slovenia; Slovenija; podjetja